ZIF-8 Modified Ce–Sol–gel Film on Rebar for Enhancing Corrosion Resistance - Zeng, Yanwei; Xu, Peng; Liu, Guoqiang; Wang, Tianguan; Lei, Bing; Feng, Zhiyuan; Zhang, Ping; Meng, Guozhe (Acta metallurgica sinica : English letters, 2024)
Chloride-induced corrosion of steel reinforcement is the key factor leading to the degradation of reinforced concrete building durability. Improving the corrosion resistance of oxide scale of rebar has always been a research hotspot in the field of civil engineering materials. A ZIF-8 modified Ce–Sol–gel (ZCS) film was prepared on oxide scale of plain steel rebars by sol–gel method. It is observed that the | Z | 0.01 Hz value of the ZCS film reached 320 kΩ cm 2 , which is about 29 times higher than that of blank rebar in simulated concrete pore (SCP) solution with 0.1 M NaCl. Then, they were inserted into mortar block and curing them in a curing box at T = 20 ± 2 °C and RH = 95 ± 2% for 28 days. Subsequently, these samples were subject to electrochemical impedance spectroscopy in 3.5 wt% NaCl. The | Z | 0.01 Hz value of the rebar with the ZCS film was six times higher than that of the blank rebar after immersing for 20 days, resulting in an overall increase in corrosion resistance for rebar. The results indicated that the modification by ZIF-8 could reduce the porosity of Ce–sol–gel (CS) film and improved the “labyrinth effect” of the film. Additionally, the negative charge on the surface of ZIF-8 in alkaline condition increased the repulsion effect with Cl − , significantly reducing the sensitivity of rebar to Cl − .